2019
DOI: 10.1155/2019/5410672
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Retinal Perfusion in Children, Adolescents, and Young Adults with Type 1 Diabetes Using Optical Coherence Tomography Angiography

Abstract: We performed a cross-sectional study to analyze the retinal vasculature in children, adolescent, and young adults with type 1 diabetes using optical coherence tomography angiography (OCTA). Patients underwent funduscopic examination for diabetic retinopathy (DR) screening during an annual visit for the screening of diabetes-related complications which included the evaluation of glycated hemoglobin (HbA1c), microalbuminuria, lipid profile, arterial pressure, and neurological assessment. In addition, OCTA of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
0
26
2
Order By: Relevance
“…In our study, this parameter negatively correlated with FAZ. This is contrary to the research by Onoe et al, where the larger FAZ area was associated with the older onset age [ 20 ] or to the study of Mameli et al, in which the correlation was not statistically significant [ 21 ]. Nevertheless, the number of participants in the aforementioned studies was remarkably smaller in comparison with our analysis.…”
Section: Discussioncontrasting
confidence: 98%
“…In our study, this parameter negatively correlated with FAZ. This is contrary to the research by Onoe et al, where the larger FAZ area was associated with the older onset age [ 20 ] or to the study of Mameli et al, in which the correlation was not statistically significant [ 21 ]. Nevertheless, the number of participants in the aforementioned studies was remarkably smaller in comparison with our analysis.…”
Section: Discussioncontrasting
confidence: 98%
“…25 The largest series in type 1 DM have been described in children, and they interestingly have shown controversial results. [26][27][28][29][30] Golebiewska et al reported that no differences were seen in the VD or FAZ area in any of the studied plexuses between patients with type 1 DM and controls (n = 188 vs. 60); however, Niestrata-Ortiz et al described that FAZ area was different between diabetic and healthy children (n = 112 vs. 30). 27,28 In this last paper, a greater FAZ area was also associated with a longer duration of the disease.…”
Section: Discussionmentioning
confidence: 92%
“…DR is uncommon before puberty, and there are only a few OCTA studies on children with T1D. Some of them have found no differences in macular OCTA parameters between T1D without DR and controls [23,24], while others have found children with T1D without DR to have significantly lower VD in the DCP and larger FAZ than controls [25][26][27]. Puberty significantly increases the risk of DM complications; hence, adolescence is the time when efforts should be directed to screening for early signs of DR and modifiable risk factors [2]; therefore, patients aged 15-30 years with T1D with at least 10 years of diabetes duration are a very important age group.…”
Section: Introductionmentioning
confidence: 99%